2015
DOI: 10.1111/phpp.12155
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lung cancer in patients with systemic sclerosis treated with extracorporeal photopheresis

Abstract: We confirm that SSc patients are at significantly increased risk for lung cancer. However, ECP does not influence this risk. NSIP may be a risk factor for lung cancer in SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…Unfortunately, in the current study, only seven patients had lung cancer of stage IIIA or lower, and six of whom had received surgery. The median survival time of SSc patients with lung cancer was 1.4 years, which was similar to that reported by Topuzoglu et al (14 months)23 but much shorter than that of non-SSc patients with lung cancer (~3 year) 24. It has been reported that EGFR gene mutation and ALK gene rearrangement are more common in non-smoking young female patients with lung adenocarcinoma 26,27.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Unfortunately, in the current study, only seven patients had lung cancer of stage IIIA or lower, and six of whom had received surgery. The median survival time of SSc patients with lung cancer was 1.4 years, which was similar to that reported by Topuzoglu et al (14 months)23 but much shorter than that of non-SSc patients with lung cancer (~3 year) 24. It has been reported that EGFR gene mutation and ALK gene rearrangement are more common in non-smoking young female patients with lung adenocarcinoma 26,27.…”
supporting
confidence: 85%
“…In the present study, lung cancers were detected in three patients via regular annual chest CT for ILD. Previous study suggests that ILD usually develops and progresses during the first 8 years of SSc onset, 23 and then, ILD gradually becomes stable. Thus, the intervals between CT scanning at our centre were prolonged to reduce radiation damage from high‐resolution chest CT.…”
Section: Discussionmentioning
confidence: 91%
“…Confirming larger meta‐analyses, the risk for lung cancer in SSc patients was increased by 2.34 [95% confidence interval (CI) 1.63–2.49] 20,21 . However, ECP therapy did not affect the risk of lung cancer in patients with SSc 19 …”
Section: Sclerodermamentioning
confidence: 70%
“…Finally, a retrospective study by Topuzoglu et al . evaluated the incidence of lung cancer in 71 SSc patients treated with ECP between 1991 and 2013 19 . Confirming larger meta‐analyses, the risk for lung cancer in SSc patients was increased by 2.34 [95% confidence interval (CI) 1.63–2.49] 20,21 .…”
Section: Sclerodermamentioning
confidence: 84%
“…The effect of ECP was also investigated in randomized, double blind, placebo controlled studies with varying outcome, ranging from no improvement against no treatment, improvement over no treatment but no improvement against sham to a superiority of ECP against D-penicillamine treatment (5360). Patients with scleroderma may have a higher risk in developing lung cancer, but no difference was found between patients with ECP and patients without ECP treatment (61). …”
Section: Indicationsmentioning
confidence: 99%